Inadecuada atención integral a personas con discapacidad del barrio Collingora, parroquia Santa Teresita, cantón Espíndola, en la actualidad - Torres Torres, Blanca Soledad (2025)
This study analyzes the issue of inadequate comprehensive care for people with disabilities in the Collingora neighborhood, Santa Teresita parish, Espíndola canton, focusing on their limited access to essential services and inclusive policies. The objective was to identify the causes and consequences of this problem and propose strategies to improve the living conditions of this vulnerable population. A mixed-methods approach was applied, utilizing qualitative and quantitative techniques, including surveys and interviews with people with disabilities, their families, and local representatives. The cross-sectional design captured a comprehensive view of the current situation. Key findings reveal that 76% of respondents believe there is inadequate access to local services, while 85% perceive that authorities fail to prioritize the rights of people with disabilities. Furthermore, 40% report limited family support, directly affecting the well-being of affected individuals. These results highlight the gap between established policies and their effective implementation in rural communities. Conclusions indicate that inadequate comprehensive care is linked to resource shortages, the absence of inclusive programs, and a lack of awareness among local authorities. Recommendations include strengthening community networks, implementing targeted public policies, and ensuring equitable access to basic services, with a focus on economic, educational, and social inclusion. This study provides a foundation for future research aimed at improving the living conditions of people with disabilities in similar rural contexts